Deng Linlin - Kroeff, Ricardo Koch (2015)
This is a work for the Master in Creative Writting and is formed by two parts: a book with short stories (part one, called Deng Linlin) and essays (part two, called Linlin Deng) about that same fiction. This writtings are all in connection with surrealism and with the place where dreams fall asleep. Realism is here too, but only in situations where, if you were there, would question yourself: is this a dream? The first essay is about narrative, about details and specific techniques of story telling. The second essay is more abstractive, and searches the place of coincidences in the creative process, where do they belong and what do they mean. The last essay is an analisys of Bob Dylan’s style in song writting. This analysis was used for emulating his voice in one of the short stories.